Pengaruh Inflasi dan Pertumbuhan Ekonomi terhadap Tingkat Pengangguran Terbuka di DKI Jakarta Tahun 2005-2022 - Hidayat, Syahrul (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2024)
Every country has the challenge of overcoming the problem of poverty because every year, population growth results in an increase in the number of job seekers. If this increase in labor demand is not met by the labor market, the poverty rate will rise. It is impossible to disentangle diverse causes, such as inflation and economic growth, from changes in poverty rates. The result of the test for the inflation regression coefficient is 1.725156. Accordingly, if inflation rises, open poverty will also rise by 1.725156%, and since the probability associated with the inflation variable is 0.0000, this indicates that inflation significantly affects open grasslands in DKI Jakarta from 2005 to 2022. The economic growth regression coefficient's outcome is now 0.281314. Since the probability associated with the economic growth variable is 0.0001, it follows that if economic growth grows, there will be an increase in open unemployment of 0.281314, indicating that it has a positive and large impact on the amount of open unemployment